Mental Health Legislation and Involuntary Commitment in Nigeria: A Call for Reform - Andrew Hudson Westbrook (Washington University Global Studies Law Review, 2011)
The Article focuses on the mental health issues in Nigeria which is governed by the colonial law and the Mental Health Act sponsored by the Nigerian National Assembly. It further provides an overview of the mental health legislation that is currently being followed and about the provisions of the new Act. It also focuses on the amendments to be made in the Mental Health Act based on the recommendations provided by the World Health Organization (WHO).
Keywords: Mental health laws; Colonies – Law & amp; legislation; Legislative amendments; World Health Organization